A distant shore [large type] - Kingsbury, Karen (Wheeler Publishing large print hardcover, 2021)
"She was a child caught in a riptide in the Caribbean Sea. He was a teenager from the East Coast on vacation with his family. He dove in to save her, and that single terrifying moment changed both their lives forever. Ten years later Jack Ryder is a daring secret agent with the FBI, and Eliza Lawrence still lives on that pristine island. She's an untainted princess in a kingdom of darkness and evil, on the brink of a forced marriage to a dangerous drug lord. When Jack and Eliza meet again, there's a connection neither of them can explain. Both their lives are on the line, and once again, the stakes are deadly high"--Page 4 of cover.